Transforming Pedagogy: The Digital Revolution in Higher Education - Nizar Bitar; Nitza Davidovich (MDPI AG, 2024)
The rapid integration of Digital Learning into higher education, accelerated by the COVID-19 pandemic, has transformed educational landscapes globally. This qualitative study employs a phenomenological approach, through thematic analysis of in-depth interviews with 15 lecturers, to investigate the implementation of a Digital Learning initiative by the Council for Higher Education (CHE) and the Planning and Budgeting Committee (PBC) at a leading institution in northern Israel. Our findings reveal four interconnected domains influencing Digital Learning implementation: educational, personal, cultural and social, and institutional. We found that while Digital Learning enhances pedagogical innovation and accessibility, it also presents significant challenges in terms of technological adaptation and cultural integration. This study provides strategic recommendations for refining Digital Learning strategies and offers unique insights into implementing Digital Learning in a culturally diverse, technologically advanced setting. Key recommendations include developing culturally responsive Digital Learning environments, integrating traditional practices like 'chavruta' into digital platforms, and investing in flexible technological infrastructure to support diverse pedagogical approaches within the unique Israeli educational context.